2019
DOI: 10.1177/0003319719844678
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Protein Microarray for Simultaneous Analysis of 274 Cytokines Between Abdominal Aortic Aneurysm and Normal Aorta

Abstract: Cytokines play an important role in the pathogenesis of abdominal aortic aneurysm (AAA). We evaluated the cytokine expression profile of large AAA walls using a 274-cytokine protein array. We hypothesized that AAAs are characterized by an inflammatory, chemotactic cytokine profile. We investigated the cytokine expression profile of 12 patients with AAA and 6 nonaneurysmal controls using an antibody-based protein array. The array generated antibodies against homogenized human aortic tissues to validate the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…This result suggests that enhanced angiogenesis is involved in the AAA pathogenesis, as PDGFA is a strong stimulator of this process [38,39]. A similar result for PDGFA was obtained in previous studies using a membrane-based complementary DNA expression array and immunohistochemical staining of tissues, in which PDGFA was significantly upregulated in AAA compared to the control samples [40,41]; however, the other study showed lower expression of PDGFA in aneurysm vs. normal aorta [42]. This discrepancy could result from a type of aneurysm and the site where tissue sample was collected, since, previously, a higher expression of PDGFA, together with PDGFB, was detected in small vessels of the aneurysmal walls of atherosclerotic AAA, but in inflammatory AAA this expression was significantly lower [43].…”
Section: Discussionsupporting
confidence: 84%
“…This result suggests that enhanced angiogenesis is involved in the AAA pathogenesis, as PDGFA is a strong stimulator of this process [38,39]. A similar result for PDGFA was obtained in previous studies using a membrane-based complementary DNA expression array and immunohistochemical staining of tissues, in which PDGFA was significantly upregulated in AAA compared to the control samples [40,41]; however, the other study showed lower expression of PDGFA in aneurysm vs. normal aorta [42]. This discrepancy could result from a type of aneurysm and the site where tissue sample was collected, since, previously, a higher expression of PDGFA, together with PDGFB, was detected in small vessels of the aneurysmal walls of atherosclerotic AAA, but in inflammatory AAA this expression was significantly lower [43].…”
Section: Discussionsupporting
confidence: 84%
“…In this view, recently, we documented that vascular damage induces an inflammatory response that can evoke a local reaction with the activation and recall of cytokines and inflammatory mediators [33] involved in aneurysmal diseases [32,34]. In an interesting pilot study, Yuwen et al [35], investigating the expression of a plethora of cytokines in patients with aortic aneurysmal disease compared to healthy patients, described the role of several cytokines (i.e., CC chemokines, CXC chemokines, proinflammatory cytokines, growth factors, proteolytic proteins, and cell adhesion cytokines) in the pathogenesis of the aneurysms. In this study, several cytokines (e.g., IL-1α, IL-1β, IL-2, and IL-17) and growth factors (e.g., insulin-like growth factor-1, transforming growth factor-α, and tumor necrosis factor-α) were reported to activate NGAL, a marker of neutrophil activation [36] that is involved in tissue injury [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…In accordance with previous reports, some proinflammatory cytokines, chemokines, proteolytic proteins, and aneurysmrelated GO entries were identified in the pathogenesis and development of AAA. 27,28 By using the emerging singlecell sequencing technique, we further explored the cell-specific expression of these hub genes. The PPI and single-cell sequencing analysis identified four hub genes involved in the progression of AAA.…”
Section: Discussionmentioning
confidence: 99%